PELATIHAN OPTIMALISASI BIAYA MODAL BAGI PEBISNIS PEMULA - Dasman, Sunita (Jurnal Pelita Pengabdian, 2025)
Financial management is a crucial aspect that determines the success and sustainability of a business. One of the key elements in financial management is understanding and managing the cost of capital. The training program "Optimizing Cost of Capital for Novice Entrepreneurs" is designed to help business owners especially Small Medium Enterprises (SME’s) to understand the concepts, components, and strategies for managing the cost of capital effectively. The training should be designed using interactive, practical, and outcome-based methods to ensure participants comprehend the concept of the cost of capital and can apply it effectively. At the end of the session, feedback will be provided to measure participants' understanding. The next step involves mentorship to ensure the implementation of the cost of capital concepts in real business scenarios.